CCDC80 protects against aortic dissection and rupture by maintaining the contractile smooth muscle cell phenotype - Xiao, Qingqing; Li, Yi; Cai, Bin; Huang, Xiying; Fang, Liang; Liang, Feng; Chen, Long; Xu, Ke; Zhang, Weifeng; Wang, Xiaolei; Yin, Anwen; Wang, Xia; et al. (Advanced science, 2025)
Aortic dissection (AD) is a life-threatening medical emergency characterized by adverse vascular remodeling. Coiled-coil domain-containing protein 80 (CCDC80) plays an essential role in regulating cardiovascular remodeling. This study aims to define the role of CCDC80 in the formation and development of AD. Significant downregulation of CCDC80 in vascular smooth muscle cell (VSMC) in human and mouse AD is identified. Then, CCDC80 knockout mice (CCDC80−/−) and VSMC-specific CCDC80 knockout mice (CCDC80fl/fl SM22α Cre+) treated with angiotensin II (Ang II) or Ang II combined with β-aminopropionitrile monofumarate (BAPN) frequently develop AD with higher frequency and severity, accompanied by severe elastin fragmentation and collagen deposition. Mechanistically, CCDC80 interacts with JAK2, and CCDC80 deficiency promotes VSMC phenotype switching, proliferation, and migration as well as matrix metalloproteinase production by activating the JAK2/STAT3 signaling pathway. Moreover, the JAK2/STAT3 pathway-specific inhibitor ameliorates adverse vascular remodeling and reduces AD formation in CCDC80-knockout mice by mitigating VSMC phenotype switching. In conclusion, CCDC80 deficiency exacerbates the progression of events leading to AD by activating the JAK2/STAT3 pathway involved in regulating the phenotype switching and function of VSMCs. These findings highlight that CCDC80 is a potential key target for the prevention and treatment of AD.
Erstmals veröffentlicht: 25. April 2025
Gesehen am 03.07.2025